Implementation of Activity-Based Costing Method in Calculating Kebab Production Cost at TIME420S Langowan - Oroh, Sherenity Debora Christy; Pusung, Rudy J.; Lintong, Diana (Formosa Journal of Applied Sciences, 2024)
This study aims to apply the Activity-Based Costing (ABC) method in calculating the Cost of Goods Sold (COGS) of kebabs at Time420s Langowan. The application of the ABC method in this business includes identifying various activities related to kebab production and allocating costs based on the volume cost driver. The method used in this study is qualitative descriptive and uses data collection techniques in the form of interviews. Based on the calculation, the COGS for each kebab is Rp. 23,313, with a total monthly COGS reaching Rp. 26,040,420. The results of the study showed that the ABC method proved to be more accurate and fair in allocating costs because it uses cost drivers according to activities such as ingredient preparation, cooking, and electricity usage, so that COGS is more relevant to the resources used.